Investigation of deformation in irregular excavations and soil disturbance in highly sensitive soft ground regions - Bao, XiYan; Fang, ZhongQiang; Lv, JinYang; Lu, LinTong; Yuan, JingHan (Frontiers in Earth Science, 2025)
In soft soil regions, the construction of irregular-shaped excavations can readily disturb the underlying soft clay, leading to alterations in soil properties that, in turn, cause significant deformations of the excavation support structure. These deformations can compromise both the excavation’s stability and the surrounding environment. Based on a large-scale, irregular-shaped excavation project for an underground interchange in a soft soil area, numerical simulations were performed using Midas GTS to analyze the overall foundation pit deformationn. The study explored the effects of groundwater lowering, excavation, and local seepage on the disturbance of surrounding soils and the resulting foundation pit deformationn. The findings reveal that the irregular-shaped excavation exhibits distinctive spatial deformation characteristics, with the arcuate retaining structure’s “arching” effect reducing the diaphragm wall’s horizontal displacement. Groundwater lowering exerts a stronger disturbance on shallow soils near the excavation and a weaker disturbance on deeper soils. Excavation-induced stress redistribution notably affects the soils above the excavation surface and those within the embedded region of the support structure. Local seepage primarily disturbs the soils surrounding the leakage point. Additionally, the weakening of soil parameters significantly influences the foundation pit deformationn. Combined disturbance (dewatering + excavation + leakage) induced 32%, 45%, and 58% greater displacements compared to individual factors, confirming the critical role of multi-factor coupling effects.